Knowledge attitude practice and acceptance of postpartum intrauterine devices among postpartal women in a tertiary care center - Yadav, Sumitra; Joshi, Ruchi; Solanki, Monica (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: PPIUCDs are the only method for couples requesting a highly effective and reversible, yet long acting, family planning method that can be initiated during the immediate postpartum phase. World Health Organization (WHO) medical eligibility criteria state that it is generally safe for postpartum lactating women to use a PPIUCD, with the advantages outweighing the disadvantages. PPIUCDs are cost-effective and they are low-cost intervention that reduces maternal, infant, and under-five Child mortality. Methods: After approval from the ethical committee and consent from the patients, the study was performed on 1000 postpartum women within 10 min. of delivery and up to 6 weeks of delivery at Labour Room of, M.Y. Hospital, Indore. Results: Majority of acceptor (72.5%) belong to age group of 18-25 years and 53% belonged to urban area. Acceptance was more in those who completed their secondary school level education (33%). Working women (55.5%) accepted PPIUCD more than the non-working. Out of 1000 women counselled only 10% agreed for PPIUVD insertion. During the study of 1 year duration (3.5%) of non-acceptors become pregnant and none of the acceptors conceived. Most common reason stated for accepting PPIUCD among acceptors, was that it is a reversible method (66%). Most common reason for not accepting PPIUCD among non-acceptors, because they are interested in Other Method of Family Planning (60%). Conclusions: Verbal acceptance is more than actual insertion of PPIUCD because of adoption of other method of family planning, family pressure, nonacceptance by partner, lack of awareness, fear of complication. Proper counselling can help to generate awareness and compliance for PPIUCD use in postpartum mother who have institutional delivery. Inserting CuT 380A within 10 min after placental delivery is safe and effective, has high retention rate. The expulsion rate was not high, and further can be reduced with practice could not be predicted.